1995
DOI: 10.1037/0022-3514.69.1.58
|View full text |Cite
|
Sign up to set email alerts
|

A new look at motivated inference: Are self-serving theories of success a product of motivational forces?

Abstract: People construct idiosyncratic, self-serving models of excellence or success in social domains, in part, to bolster self-esteem. In 3 studies, participants tended to articulate self-serving theories of success under experimental conditions in which pressures to maintain self-esteem were present, but not under conditions in which such pressures were absent. Participants assigned to role-play being a therapist were more self-serving in their assessments of the characteristics needed to be a "successful therapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 47 publications
9
152
1
2
Order By: Relevance
“…It is important to note how the current research relates to work within the self-enhancement tradition, which argues that individuals are driven to be confident because it provides them with psychological benefits (Dunning, Leuenberger, & Sherman, 1995;Kunda, 1987). That work has shown that believing in oneself simply feels good (Marshall & Brown, 2008;Sedikides & Gregg, 2008).…”
Section: The Origins Of Overconfidencementioning
confidence: 99%
“…It is important to note how the current research relates to work within the self-enhancement tradition, which argues that individuals are driven to be confident because it provides them with psychological benefits (Dunning, Leuenberger, & Sherman, 1995;Kunda, 1987). That work has shown that believing in oneself simply feels good (Marshall & Brown, 2008;Sedikides & Gregg, 2008).…”
Section: The Origins Of Overconfidencementioning
confidence: 99%
“…For years, researchers have documented numerous self-serving biases, such as the tendency to see oneself as above average on positive characteristics such as intelligence (when, of course, not everyone can be above average), to overrate one's role in group projects with positive outcomes, and so forth (see Dunning, Leuenberger, & Sherman, 1995 ;Epstein, 1992 ;Greenwald & Pratkanis, 1984 ). More recent research has begun to track down individual differences in the tendency to see ourselves unlike others see us, and has found, as clinical observation suggests, that narcissistic people tend to hold defensively grandiose views of themselves and their accomplishments and that this is not without substantial social and personal cost.…”
Section: Other Studies Documenting Unconscious Emotional Processesmentioning
confidence: 99%
“…On the one hand, we see a concern for the reliability (or lack thereof) of our cognitive systems in the literature that deals with dual-process theories of cognition, heuristics, and biases (Epstein, Lipson, Holstein, & Huh, 1992;Evans, 2007;Gilovich, 1991;Gilovich, et al, 2002;Kahneman, 2011;Sloman, 2002;Stanovich, 1999). On the other hand, there is a concern for responsibilism reflected in a focus on the role of motivation in cognition and cognitive bias (Chaiken, et al, 1996;Dunning, et al, 1995;Kunda, 1990;Wegener & Petty, 1997). It is not as if those concerned with heuristics and biases ignore the role of motivation (Evans, 2007;Stanovich & West, 1997) nor do those primarily interested in the role of motivation ignore cognitive mechanisms and capacity (Chaiken, et al, 1996).…”
Section: §3 the Virtuous Knowermentioning
confidence: 99%
“…12 The examples of behaviors and techniques noted above that help to reduce biases share the common aspect of "de-centering" (decoupling) thought to include and consider the "other" through the use of rules of reasoning, a concern for accuracy, a need for accountability, and taking the perspective of others. One common theme in the literature is the role of motivation in de-biasing thought (Chaiken, et al, 1996;Dunning, et al, 1995;Kunda, 1990;Wilson, et al, 2002), pointing to the conclusion correcting biases is an effortful process that requires some kind of motivation to overcome the self-centered tendencies of our cognitive system. In this way, it reflects the neo-Aristotelian (responsibilist) notion of epistemic virtue: that it must be consciously practiced to overcome our more arrogant cognitive tendencies and avoid the possibility of being too diffident to others by giving in too easily or not evaluating the other's position rigorously.…”
Section: §322 Accuracy and Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation